Insights Into Cerebral Tissue-Specific Response to Respiratory Challenges at 7T: Evidence for Combined Blood Flow and CO2-Mediated Effects - Champagne, Allen A.; Bhogal, Alex A. (Frontiers in Physiology, 2021)
Cerebrovascular reactivity (CVR) mapping is finding increasing clinical applications as a non-invasive probe for vascular health. Further analysis extracting temporal delay information from the CVR response provide additional insight that reflect arterial transit time, blood redistribution, and vascular response speed. Untangling these factors can help better understand the (patho)physiology and improve diagnosis/prognosis associated with vascular impairments. Here, we use hypercapnic (HC) and hyperoxic (HO) challenges to gather insight about factors driving temporal delays between grey-(GM) and white-matter (WM). BOLD datasets were acquired at 7T in nine healthy subjects throughout BLOCK- and RAMP-HC paradigms. In a subset of seven participants, a combined HC + HO block, referred as the “BOOST” protocol, was also acquired. Tissue-based differences in Rapid Interpolation at Progressive Time Delays (RIPTiDe) were compared across stimulus to explore dynamic (BLOCK-HC) versus progressive (RAMP-HC) changes in CO2, as well as the effect of bolus arrival time on CVR delays (BLOCK-HC versus BOOST). While GM delays were similar between the BLOCK- (21.80+/-10.17 seconds) and RAMP-HC (24.29+/-14.64 seconds), longer WM lag times were observed during the RAMP-HC (42.66+/-17.79 seconds), compared to the BLOCK-HC (34.15+/-10.72 seconds), suggesting that the progressive stimulus may predispose WM vasculature to longer delays due to the smaller arterial content of CO2 delivered to WM tissues, which in turn, decreases intravascular CO2 gradients modulating CO2 diffusion into WM tissues. This was supported by a maintained ~10 s offset in GM (11.66+/-9.54 seconds) versus WM (21.40+/-11.17 seconds) BOOST-delays with respect to the BLOCK-HC, suggesting that the vasoactive effect of CO2 remains constant and that shortening of BOOST delays was be driven by blood arrival reflected through the non-vasodilatory HO contrast. These findings support that differences in temporal and magnitude aspects of CVR between vascular networks reflect a component of CO2 sensitivity, in addition to redistribution and steal blood flow effects. Moreover, these results emphasize that the addition of a BOOST paradigm may provide clinical insights into whether vascular diseases causing changes in CVR do so by way of severe blood flow redistribution effects, alterations in vascular properties associated with CO2 diffusion, or changes in blood arrival time.